HUBUNGAN KARAKTERISTIK INDIVIDU DAN PENYAKIT PENYERTA DENGAN KUALITAS HIDUP PENDERITA DIABETES MELLITUS - Santoso, Raden Bagus Edy; Ernita, Ernita; Sutiswa, Shandra Isasi; Yulianita, Yulianita; Noorma, Nilam (Ensiklopedia of Journal, 2024)
Abstract: Diabetes mellitus (DM) is a non-communicable disease that occurs due to very high blood sugar levels. Based on data search, it is known that Pulomerak Health Center is the health center with the highest DM cases in Cilegon City with 920 cases. The purpose of the study was to determine the relationship between individual characteristics and comorbidities with the quality of life of patients with diabetes mellitus. The type of research is quantitative research with a cross sectional design. The research was conducted in May 2023 at Pulomerak Health Center. The sample amounted to 163 people. The sampling technique used probability sampling with simple random sampling technique. The research instrument used a research questionnaire. Data analysis was carried out univariate and bivariate. The results showed that there was a relationship between individual characteristics, namely age (p value: 0.009) and comorbidities (p value: 0.000) on the quality of life of patients with diabetes mellitus. It is recommended for diabetics to not only carry out examinations related to DM disease but comorbidities suffered also really need to be checked to monitor their health conditions so as to prevent complications and not interfere with daily activities which will then have a positive impact on their quality of life and for Puskesmas to improve health services to DM sufferers not only in DM treatment but also can pay attention to the quality of life.Keywords: Diabetes Mellitus, Comorbidities, Age.